100 Years of earthquakes in the Pamir region as recorded in juniper wood: A case study of Tajikistan. (1st May 2017) - Owczarek, Piotr; Opała-Owczarek, Magdalena; Rahmonov, Oimahmad; Mendecki, Maciej
Graphical abstract: Highlights: The first dendroseismological study from the Pamir-Alay. Tree-ring data show links between juniper growth and earthquakes. Earthquakes trigger soil shaking and affect the juniper growth suppression. Characteristic growth-ring patterns will enable the reconstruction of seismic events. Indication of the earthquakes in tree-ring data improves dendroclimatic reconstruction. Abstract: Active tectonics reflect high seismicity rates in the Pamir and surrounding areas. Long-lived trees growing in the western Pamir-Alay mountains are affected by ground accelerations and seismic-induced geomorphic processes. At a high-mountain site in the Pamir-Alay, 45 juniper trees were sampled in order to analyze the potential role of these trees in the reconstruction of disturbance events. Although the trees have a maximum age c. 500 years, only the period of the last 100 years was analyzed, aiming for the dendrochronological identification of earthquake events known by historic documents and measurements. Analysis mainly showed non-climatic growth suppression and releases. These signals were identified as the results of tectonic disturbances. Tree-ring data recorded many earthquakes from which the most distinct were: 1907, 1923, 1943, 1955, 1982, and 1998. The 1907 and 1923 large earthquakes took place after the vegetation period; therefore, growth reduction appeared in the following year. The 1943, 1955, 1982, and 1998 events occurred just before or during the vegetation period and therefore induced the immediate reduction of tree rings in the earthquake year. The identification of the characteristic growth ring patterns, which are a response to large earthquakes, will enable the reconstruction of these events in the past on the basis of centuries-long dendrochronological records.